Sphingosine-1-Phosphate Phosphohydrolase Regulates Endoplasmic Reticulum-to-Golgi Trafficking of Ceramide - Giussani, Paola (American Society for Microbiology (ASM), 2006)
Previous studies demonstrated that sphingosine-1-phosphate (S1P) phosphohydrolase 1 (SPP-1), which is located mainly in the endoplasmic reticulum (ER), regulates sphingolipid metabolism and apoptosis (H. Le Stunff et al., J. Cell Biol. 158:1039-1049, 2002). We show here that the treatment of SPP-1-overexpressing cells with S1P, but not with dihydro-S1P, increased all ceramide species, particularly the long-chain ceramides. This was not due to inhibition of ceramide metabolism to sphingomyelin or monohexosylceramides but rather to the inhibition of ER-to-Golgi trafficking, determined with the fluorescent ceramide analog N-(4,4-difluoro-5,7-dimethyl-4-bora-3a,4a-diaza-s-indacene-3-pentanoyl)-d-erythro-sphingosine (DMB-Cer). Fumonisin B1, an inhibitor of ceramide synthase, prevented S1P-induced elevation of all ceramide species and corrected the defect in ER transport of DMB-Cer, readily allowing its detection in the Golgi. In contrast, ceramide accumulation had no effect on either the trafficking or the metabolism of 6-([N-(7-nitrobenzo-2-oxa-1,3-diazol-4-yl)amino]hexanoyl)-sphingosine, which rapidly labels the Golgi even at 4°C. Protein trafficking from the ER to the Golgi, determined with vesicular stomatitis virus ts045 G protein fused to green fluorescent protein, was also inhibited in SPP-1-overexpressing cells in the presence of S1P but not in the presence of dihydro-S1P. Our results suggest that SPP-1 regulates ceramide levels in the ER and thus influences the anterograde membrane transport of both ceramide and proteins from the ER to the Golgi apparatus.